STRATEGI SEGMENTING, TARGETING AND POSITIONING (STP) PADA APLIKASI PELAPORAN PAJAK VERSI EDUKASI - isti Pri hanani (Pusat P2M Politeknik Negeri Batam, 2023)
This research was conducted to analyze data on understanding tax returns using electronic filing and respondents' level of need for the educational version of the tax return application. The researchers used a qualitative descriptive method with an intentional sampling technique. Analytical techniques are used to process the data through the results of the distribution of the questionnaires. The results showed that not 100% of respondents understood the tax reporting obligations of individual taxpayers, particularly in the E-Filling tax return application, and Respondent interest in the educational version of the tax filing application remains low, with 25.6% of 39 respondents choosing the lowest price range and expecting the educational version of the tax filing application to pay for the educational version of the tax filing application. I replied that I would. as an instrument of government. In the world of education for free access to provide hands-on experience to beneficiaries.